Determinants of the financial liquidity of local governments: Empirical evidence from Poland - Galiński, Paweł (Publishing House of Wroclaw University of Economics and Business, 2023)
The aim of this paper was to examine the financial, economic and social factors as well as spatial relations influencing the level of the financial liquidity of local governments. In the study research, logistic regression models were applied as well as Moran’s I statistic concerning the spatial autocorrelation on the counties in Poland. According to the data for the period 2018-2020, there were estimated regressions for each year and the longitudinal models. The results of the models’ calculation and validation indicated that they might be used to define the level of liquidity in the local public units, since this liquidity influences the local economic condition and the range of public service delivery. The findings show that the predictors of the cash position have both an internal and an external character. Some of these factors appear constantly and result from the situation of the operating part of the local budget. Hence, the fiscal capacity is crucial in this field and the share of own revenues. A debt burden might also determine the analysed liquidity, as well as the size of the unit, which is in line with the presented findings of other scholars, therefore it is important to constrain the growth of the fixed costs and make the local budget more flexible. On the other hand, the share of students in the population is significant due to the fact this influences the scope of public tasks in the field of education. Thus, the local units have real instruments to manage their financial liquidity, which is mainly affected by the transactions-motive and the precautionary-motive. Analysing the spatial structure on the financial liquidity, there is a weak, negative spatial correlation in this field. The study also revealed the phenomenon of ‘outliers’. To sum up, there are specific fiscal and socio-economic characteristics of the local public units affecting their cash positions, which is also influenced by the spatial structure.
Argumenta Oeconomica, 2023, Nr 2 (51), s. 131-154
Keywords: financial liquidity; local government; ordered logistic regression; spatial autocorrelation